Magneto-optical transverse Kerr effect in Cox(CoO)1−x nanocomposites - Maxim M. Yashin; Vitaly E. Ryabukhin; Alexey N. Yurasov (Российский технологический журнал)
Objectives. The aim of this paper is to attain and investigate the spectra of the magneto-optical transverse Kerr effect (TKE) in Cox(CoO)1−x nanocomposites, to compare the obtained results with experimental data, and identify their specific features. Magneto-optical spectroscopy is a method for non-destructive testing and research of a wide class of nanostructures with promising and interesting properties, and such studies are essential in terms of both fundamental and practical aspects.Methods. Computer modeling is used as part of the promising effective medium method. This is in the form of the Bruggeman approximation, according to which the structure under study is replaced by a medium with effective properties.Results. TKE experimental spectra were studied and Kerr effect spectra in the range of 1.5–3.0 eV were obtained by computer modeling. In this case, the modeling is performed by means of two methods, ignoring and considering the quasiclassical size effect. The final result is the comparison of the model and experimental Kerr effect spectra, in which the influence of size effects on the appearance of the TKE spectra is shown. The reliability of methods is well confirmed by comparing the results obtained with empirical data. The value of the results obtained stems from the fact that all the calculated parameters of the nanocomposite under study and the shape of TKE spectral dependencies  are in good agreement with the observation results.Conclusions. The optimal parameters of the sample under study are established as part of computer modeling: form factor, average granule size, and the anomalous Hall effect coefficient. The described approach allows the magneto-optical properties of promising nanomaterials to be studied in a non-contact and non-destructive manner. These results are useful for creating new types of devices as well as electronics and nanoelectronics elements.